Childhood pneumococcal disease in Africa – A systematic review and meta-analysis of incidence, serotype distribution, and antimicrobial susceptibility. Issue 15 (4th April 2017) - Iroh Tam, Pui-Ying; Thielen, Beth K.; Obaro, Stephen K.; Brearley, Ann M.; Kaizer, Alexander M.; Chu, Haitao; Janoff, Edward N.
Highlights: Incidence, serotype and antimicrobial susceptibility data for S. pneumoniae in children in Africa. The pooled incidence of invasive pneumococcal disease (IPD) was 61.1 per 100, 000 person-years. The pooled prevalence of penicillin susceptibility to S. pneumoniae was 78.1%. Cumulatively, PCV10 and PCV13 included 66.9% and 80.6% of IPD serotypes, respectively. These data provide a reliable baseline from which to monitor the impact of broad PCV introduction. Abstract: Background: Determining the incidence, disease-associated serotypes and antimicrobial susceptibility of invasive pneumococcal disease (IPD) among children in Africa is essential in order to monitor the impact of these infections prior to widespread introduction of the pneumococcal conjugate vaccine (PCV). Methods: To provide updated estimates of the incidence, serotype distribution, and antimicrobial susceptibility profile of Streptococcus pneumoniae causing disease in Africa, we performed a systematic review of articles published from 2000 to 2015 using Ovid Medline and Embase. We included prospective and surveillance studies that applied predefined diagnostic criteria. Meta-analysis for all pooled analyses was based on random-effects models. Results: We included 38 studies consisting of 386, 880 participants in 21 countries over a total of 350, 613 person-years. The pooled incidence of IPD was 62.6 (95% CI 16.9, 226.5) per 100, 000 person-years, including meningitis which had a pooled incidence of 24.7 (95% CI 11.9, 51.6) per 100, 000 person-years. The pooled prevalence of penicillin susceptibility was 78.1% (95% CI 61.9, 89.2). Cumulatively, PCV10 and PCV13 included 66.9% (95% CI 55.9, 76.7) and 80.6% (95% CI 66.3, 90.5) of IPD serotypes, respectively. Conclusions: Our study provides an integrated and robust summary of incidence data, serotype distribution and antimicrobial susceptibility for S. pneumoniae in children ≤5 years of age in Africa prior to widespread introduction of PCV on the continent. The heterogeneity of studies and wide range of incidence rates across the continent indicate that surveillance efforts should be intensified in all regions of Africa to improve the integrity of epidemiologic data, vaccine impact and cost benefit. Although the incidence of IPD in young children in Africa is substantial, currently available conjugate vaccines are estimated to cover the majority of invasive disease-causing pneumococcal serotypes. These data provide a reliable baseline from which to monitor the impact of the broad introduction of PCV.